Metachromatic leukodystrophy - Prima Cheryl D'souza; Archanaa Vignesh; K Subaschandra; P John Mathai (Wolters Kluwer Medknow Publications, 2013)
Metachromatic leukodystrophy or Scholz's disease is a rare disorder transmitted as an autosomal recessive trait, leading to demyelination and neurological impairment. An 18-year-old boy was brought to the psychiatry out-patient department with a history of progressive decline of cognitive functions and self-help skills since 8 years. On examination, the patient was alert, easily distractible, and restless with stereotypic movements of the head. He was unable to speak, able to comprehend simple commands but not complex instructions and had an inappropriate affect. EEG revealed frequent intermittent clusters of biphasic spike-slow wave and sharpish discharges arising from bilateral fronto - centro - temporal regions. MRI brain showed non-enhancing altered signal intensity involving bilateral periventricular deep white matter, with a possibility of metachromatic leukodystrophy. Metachromatic leukodystrophy is a progressive demyelinating disorder which may present with cognitive or behavioral symptoms. It may be misdiagnosed as a psychiatric disorder, delaying intervention, leading to unnecessary exposure to neuroleptics and increasing financial burden for the family.